2017
DOI: 10.12783/dtssehs/msie2017/15479
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mobile Learning in English Teaching in Higher Vocational Colleges

Abstract: To study the development of mobile learning technology in the field of teaching, the application of mobile terminal technology in higher vocational English teaching is designed. Firstly, the present situation of basic English teaching in higher vocational colleges and the requirements of students for English learning and mobile applications are investigated and analyzed. Then, according to the analysis for previous needs, a My Word platform which is conducive to English learning has been developed. Taking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Few papers are conducted with a very specific Internet learning style as the research object. Li (2017) took English teaching in a certain college as an example and analyzed the advantages and disadvantages of Internet fragmented learning. The research showed that this kind of learning method may improve students' learning attitude [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Few papers are conducted with a very specific Internet learning style as the research object. Li (2017) took English teaching in a certain college as an example and analyzed the advantages and disadvantages of Internet fragmented learning. The research showed that this kind of learning method may improve students' learning attitude [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li (2017) took English teaching in a certain college as an example and analyzed the advantages and disadvantages of Internet fragmented learning. The research showed that this kind of learning method may improve students' learning attitude [6]. However, it will make the knowledge more fragmented, so it can not replace the role of teachers [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation